Acetyl-assisted autohydrolysis of sugarcane bagasse for the production of xylo-oligosaccharides without additional chemicals. (October 2018) - Zhang, Weiwei; You, Yanzhi; Lei, Fuhou; Li, Pengfei; Jiang, Jianxin
Graphical abstract: Highlights: XOS is produced by the acetyl-assisted autohydrolysis (AAAH) of SCB. A XOS (DP 2–5) yield of 52.99% was obtained from 65:35 SCB/WH after 10 min at 200 °C. A XOS yield of 49.64% was obtained from 65:35 SCB/WH after 100 min at 160 °C. AAAH effectively increases the contents of xylobiose and xylotriose. XOS, bioethanol, and other biochemicals could be co-produced from SCB by AAAH. Abstract: The aim of this work was to study acetyl-assisted autohydrolysis of sugarcane bagasse for the production of xylo-oligosaccharides without additional chemicals. A xylo-oligosaccharide yield of 50.35% was obtained in 10 min through sugarcane bagasse autohydrolysis at 200 °C; this yield was 49.64% after acetyl-assisted autohydrolysis of a 65:35 mixture of sugarcane bagasse/white birch at 160 °C for 100 min. The yield of xylo-oligosaccharides was close to that obtained at 180 °C/40 min and 200 °C/10 min through the autohydrolysis of sugarcane bagasse. Compared to sugarcane bagasse alone, the xylo-oligosaccharide (degree of polymerization 2–5) yield from the acetyl-assisted autohydrolysis at 200 °C for 10 min was 52.99%. In addition, the yield of glucose from the solid residue following autohydrolysis pretreatment was 96.87% after 72 h of enzymatic hydrolysis. These results demonstrate that acetyl-assisted autohydrolysis is a promising method for the production of xylo-oligosaccharides.